A Novel Mutation in DMD (c.10797+5G>A) Causes Becker Muscular Dystrophy Associated with Intellectual Disability. Issue 3 (April 2016) - Banihani, Rudaina; Baskin, Berivan; Halliday, William; Kobayashi, Jeff; Kawamura, Anne; McAdam, Laura; Ray, Peter N.; Yoon, Grace
ABSTRACT: Background: Severe intellectual disability has been reported in a subgroup of patients with Duchenne muscular dystrophy but is not typically associated with Becker muscular dystrophy. Patient: The authors report a 13-year-old boy, with severe intellectual disability (Wechsler Intelligence Scales for Children-IV, Full Scale IQ < 0.1 percentile), attention-deficit hyperactivity disorder, and mild muscle weakness. He had elevated serum creatine kinase and dystrophic changes on muscle biopsy. Dystrophin immunohistochemistry revealed decreased staining with the C-terminal and mid-rod antibodies and essentially absent staining of the N-terminal immunostain. Sequencing of muscle mRNA revealed aberrant splicing due to a c.10797+5G > A mutation in DMD . Conclusion: Dystrophinopathy may be associated with predominantly cognitive impairment and neurobehavioral disorder, and should be considered in the differential diagnosis of unexplained cognitive or psychiatric disturbance in males.